2022
DOI: 10.1155/2022/1971018
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Potential Benefits of Functional Food Characteristics of Beetroot Energy Drink and Flavored Milk

Abstract: Objective. This study was designed to determine the antioxidant activity of the extracts of beetroot by using beetroot energy drink and flavored milk (products). Material & Methods. This experimental trial was conducted at Jinnah University for Women, Pakistan, under the approval of local institutional review board number JUW/DFST/RCB010/2020. All the materials such as beetroot, carrot, cucumber, and lemon were obtained commercially from which two products were formulated: beetroot energy drink (sample1) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Dhawan et al [72] developed phytochemical rich and organoleptically acceptable beetroot Barfi and Kanjhi by incorporating beetroot flour at 1% and 4%, respectively. Similarly, Ashraf et al [73] developed a beetroot-enriched energy booster drink and flavored milk that contained high antioxidant activity, high proteins and fats, and low carbohydrates but adequate total energy content. Beetroot peels' (waste left out during the processing of beetroots) powder, which is rich in antioxidant content, has been used as a natural ingredient in several value-added emulsions, including mayonnaise, dressings, sauces, and creams [74].…”
Section: Beet Rootmentioning
confidence: 99%
“…Dhawan et al [72] developed phytochemical rich and organoleptically acceptable beetroot Barfi and Kanjhi by incorporating beetroot flour at 1% and 4%, respectively. Similarly, Ashraf et al [73] developed a beetroot-enriched energy booster drink and flavored milk that contained high antioxidant activity, high proteins and fats, and low carbohydrates but adequate total energy content. Beetroot peels' (waste left out during the processing of beetroots) powder, which is rich in antioxidant content, has been used as a natural ingredient in several value-added emulsions, including mayonnaise, dressings, sauces, and creams [74].…”
Section: Beet Rootmentioning
confidence: 99%
“…Overall, the results showed that groups ingesting beetroot juice had better results in physical exercise competitions, as well as lower pressure values, than the control group. Further, these differences appeared more marked in cases of prolonged treatment [ 160 , 161 ]. However, beetroot not only contains nitrate, but also many phytochemical compounds that can have beneficial health effects.…”
Section: Nitrates–nitrites–nitric Oxide In Fruits and Vegetablesmentioning
confidence: 99%
“…Numerous studies demonstrate that beetroot, when administered acutely as a juice supplement or in bread, dramatically lowers both systolic and diastolic blood pressure. This is especially true for hypertension, which has been the focus of many treatment strategies [8,9] . Several review articles have summarized additional discussion regarding the antihypertensive effects of beetroot.…”
Section: Introductionmentioning
confidence: 99%